Guanidinocalix[5]arene for sensitive fluorescence detection and magnetic removal of perfluorinated pollutants - Zheng, Zhe; Yu, Huijuan; Geng, Wen-Chao; Hu, Xin-Yue; Wang, Yu-Ying; Li, Zhihao; Wang, Yuefei; Guo, Dong-Sheng (Nature communications, 2019)
Perfluorinated alkyl substances, such as perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), are toxic materials that are known to globally contaminate water, air, and soil resources. Strategies for the simultaneous detection and removal of these compounds are desired to address this emerging health and environmental issue. Herein, we develop a type of guanidinocalix[5]arene that can selectively and strongly bind to PFOS and PFOA, which we use to demonstrate the sensitive and quantitative detection of these compounds in contaminated water through a fluorescent indicator displacement assay. Moreover, by co-assembling iron oxide nanoparticle with the amphiphilic guanidinocalix[5]arene, we are able to use simple magnetic absorption and filtration to efficiently remove PFOS and PFOA from contaminated water. This supramolecular approach that uses both molecular recognition and self-assembly of macrocyclic amphiphiles is promising for the detection and remediation of water pollution. Design of materials which allow for simultaneous detection and removal of water pollutants is challenging. Here the authors develop a guanidinocalix[5]arene that selectively binds perfluorinated alkyl substances and allows for fluorescence detection as well as removal of the pollutants in contaminated water.